Demographic differences and tourist preferences. Utilising the theory of planned behaviour during COVID-19/ Cheam Chai Li and Wan Muhammad Zulhilmi Wan Ya'Acob - Cheam, Chai Li; Wan Ya'Acob, Wan Muhammad Zulhilmi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This study assesses potential gender differences relating to tourist preferences (i.e. intention and frequency for travelling), knowledge, and the three variables of the Theory of Planned Behaviour (TPB). Following descriptive analysis, cross-tabulation, and independent t-tests, the results revealed that the respondents were more likely to stay at home. Cross-tabulation findings, in particular, depicted no differences for the demographic variables and respondent travel preferences. Contrarily, subjective norms and knowledge were the only two variables yielding significant mean scores with gender upon a comparison for the parameter between gender and the four major variables tested. Henceforth, the research findings are expected to serve as guidance for policymakers and industry practitioners in developing the best tourism strategies geared for gaining public trust and making travel safer and less risky for everyone.